2017
DOI: 10.1111/ane.12863
|View full text |Cite
|
Sign up to set email alerts
|

Brain signal intensity changes as biomarkers in amyotrophic lateral sclerosis

Abstract: IRhMC and HCT are reliable markers of UMN degeneration in ALS patients and are more frequent in bulbar onset patients, independently of the mutation status. Age should be considered when evaluating IRhMC. The regional measurement of IRhMC following the motor homunculus could be used as a measure of disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 38 publications
4
28
0
1
Order By: Relevance
“…In contrast, healthy controls showed no sex‐specific differences in FLAIR alterations, as reported by Gawne‐Cain et al Sex‐specific differences in FLAIR lesions were reported for MS patients despite balanced age and disease duration . In ALS research, effects of sex on FLAIR hyperintensity were not detected or not analyzed . Sex‐specific differences may be due to outliers with low TLN in the small sample size of female ALS patients ( n = 8).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…In contrast, healthy controls showed no sex‐specific differences in FLAIR alterations, as reported by Gawne‐Cain et al Sex‐specific differences in FLAIR lesions were reported for MS patients despite balanced age and disease duration . In ALS research, effects of sex on FLAIR hyperintensity were not detected or not analyzed . Sex‐specific differences may be due to outliers with low TLN in the small sample size of female ALS patients ( n = 8).…”
Section: Discussionmentioning
confidence: 68%
“…Consistent with this finding, we detected distinct effects of age on TLN and TLV. LST revealed FLAIR hyperintensity in both ALS patients and healthy controls, as reported in other studies . FLAIR lesions were observed to be dependent on sex and more frequent in male ALS patients than in female ALS patients as well as male healthy controls.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Fasciculations were most common in cervical‐innervated muscles, regardless of the region of ALS onset. Direct correlations were noted between the fasciculations and decline in body mass index, loss of sonographically measured muscle thickness, and UMN impairment, as defined by the Upper Motor Neuron Score . An inverse correlation was noted with function, as measured by the ALS Functional Rating Scale Score—Revised (ALSFRS‐R).…”
Section: Muscle Ultrasound In Alsmentioning
confidence: 92%
“…Age, gender, date of onset of motor symptoms, region of onset (bulbar and spinal), disability (ALSFRS-R) and the degree of UMN impairment (UMN score) 25 were recorded for all MND patients.…”
Section: Clinical Examinationmentioning
confidence: 99%